Evolution of Anthropometry in Malnutrition - M., Phadke; R., Nair; P., Menon; V.Singal, (International Journal of Nutrition, 2020)
The present paper describes the significance of anthropometric measurements in detecting nutritional status of individuals, specially children. It highlights evolution of anthropometry, discusses importance of various measurements & their role in determining undernutrition & obesity. There is a need to have one measurement to detect obesity & undernutrition both. An ideal such measure is yet to be established.
Keywords: Anthropometry; obesity; malnutrition